2019
DOI: 10.18632/oncotarget.27336
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen/nitrogen species contribute substantially to the antileukemia effect of APO866, a NAD lowering agent

Abstract: APO866 is a small molecule drug that specifically inhibits nicotinamide phosphoribosyltransferase (NAMPT), a key enzyme involved in nicotinamide adenine dinucleotide (NAD) biosynthesis from the natural precursor nicotinamide. Although, the antitumor activity of APO866 on various types of cancer models has been reported, information regarding mechanisms by which APO866 exerts its cytotoxic effects is not well defined. Here we show that APO866 induces a strong, time-dependent increase in highly reactive ROS, nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 59 publications
(66 reference statements)
3
23
0
Order By: Relevance
“…Although it is not BRCA-deficient, Ewing sarcoma is also characterized by defective HR (96), further supporting the idea that cancers with defective DNA repair mechanisms may have increased susceptibility to NAMPT inhibition. Interestingly, results from a recent study in preclinical leukemia models revealed functional antagonism between NAMPT and PARP inhibitors, suggesting that cell type specific differences in how these pathways interact may be present (97).…”
Section: Dna Damage Repair Responsementioning
confidence: 99%
“…Although it is not BRCA-deficient, Ewing sarcoma is also characterized by defective HR (96), further supporting the idea that cancers with defective DNA repair mechanisms may have increased susceptibility to NAMPT inhibition. Interestingly, results from a recent study in preclinical leukemia models revealed functional antagonism between NAMPT and PARP inhibitors, suggesting that cell type specific differences in how these pathways interact may be present (97).…”
Section: Dna Damage Repair Responsementioning
confidence: 99%
“…The effect of OT-82 on ROS induction in our models represents an additional example of the differential effects NAMPTis may have on different cell types. Induction of ROS is a known mechanism of NAMPTi-induced killing in a range of cancer cell types [45][46][47][48][49][50] . However, as we demonstrated in this study, induction of ROS was not responsible for OT-82-induced cell death in EWS, suggesting that ROS production is a byproduct of OT-82-induced cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of reactive oxygen species (ROS) is another commonly reported downstream effect of NAMPT inhibition [45][46][47][48][49][50] . While treatment with OT-82 resulted in at least a six-fold increase in ROS in EWS cells, addition of the antioxidant N-acetylcysteine (NAC) did not rescue cellular viability, despite reducing ROS to baseline levels, and suggests that ROS induction is not driving the antiproliferative effects of OT-82 ( Supplementary Fig.…”
Section: Ot-82 Affects Additional Nad + -Dependent Processes In Ews Cmentioning
confidence: 99%
“…And we monitored eleven batches of PNGL samples by the chemical fingerprinting assay [ 31 ]. FK866, as a highly specific NAMPT inhibitor, could inhibit the NAMPT and NAD+ biosynthesis in mammals [ 23 , 36 , 37 ]. Our present experiment has suggested the potential mechanisms in vivo .…”
Section: Methodsmentioning
confidence: 99%